“Dare to say no”: Participatory visual advocacy and the social construction of adolescent resilience against drug abuse - Wicaksono, Agung Dwi; Prianti, Desi Dwi; Oktaviani, Fitri Hariana (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
The substance abuse epidemic among adolescents is a social problem that necessitates a proactive approach that engages adolescents in the process of prevention. The objective of this study is to investigate the participatory role of adolescents in designing visual advocacy campaign media to prevent drug abuse, while also examining how this process can strengthen their social resilience. Utilizing a Participatory Action Research (PAR) framework, this study engaged adolescents aged 13–16 years in a series of workshops that fostered their involvement in the planning, production, and reflection on the campaign media. The results of the study indicate that the active involvement of adolescents in the process of creating advocacy media contributes to the strengthening of social values such as self-regulation, assertiveness, and the ability to build social support networks. In addition to producing relevant and contextual messages, this process also serves as a form of social education that empowers adolescents as agents of change. The present study lends further credence to the notion that participation-based campaign strategies and visual media have proven effective in the social education of adolescents, particularly with regard to the prevention of substance abuse.